2006
DOI: 10.1159/000093087
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Akt Phosphorylation on Tumor Growth and Vascular Endothelial Growth Factor Expression in Human Gastric Carcinoma

Abstract: Objective: Hypoxia is known to be a prevalent stress stimulus and increases the transcription of vascular endothelial growth factor (VEGF) mediated by hypoxia inducible factor-1α (HIF-1α). We investigated the role of phosphatidyl inositol-3 OH kinase (PI3K)-Akt signaling in the regulation of HIF-1α and VEGF expression in human gastric adenocarcinoma. Methods: The growth-inhibitory and apoptosis-inducing effects of the LY294002 PI3K inhibitor were analyzed in four gastric cancer cell lines and in vivo. The regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 56 publications
7
38
0
Order By: Relevance
“…Our data are in agreement with a previous study, reporting that Akt activation is related to a poor outcome in gastric cancer [41]. We also analyzed the relationship between pAkt expression and apoptotic index, because Akt has been reported to be a signal transduction protein capable of controlling the balance between cell survival and apoptosis [5,45]. It is known that phosphorylation of Akt is promoted by phosphatidylinositides converted by PI3K products at the cytoplasmatic level.…”
Section: Discussionsupporting
confidence: 91%
“…Our data are in agreement with a previous study, reporting that Akt activation is related to a poor outcome in gastric cancer [41]. We also analyzed the relationship between pAkt expression and apoptotic index, because Akt has been reported to be a signal transduction protein capable of controlling the balance between cell survival and apoptosis [5,45]. It is known that phosphorylation of Akt is promoted by phosphatidylinositides converted by PI3K products at the cytoplasmatic level.…”
Section: Discussionsupporting
confidence: 91%
“…The activation of the PI3K/AKT signaling pathway has been reported in several malignancies such as breast [32], lung [33], and head and neck carcinomas [34]. In gastric cancer, a previous study showed that the IHC expression of p-AKT was correlated with clinicopathological features such as vessel infiltration and lymph node metastasis [35]. Our study revealed that LOH of PTEN causes an activation of the PI3K/AKT signaling pathway, leading to an adverse outcome in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The serine/threonine kinase Akt plays an essential role in various cellular processes, including cell growth and proliferation, metabolism and cell survival. Immunohistochemical analyses have shown that Akt is activated in many types of carcinoma and preneoplastic lesions, and Akt activation is associated with tumor progression and poor prognosis in various human malignancies [23][24][25][26][27] . However, in NSCLCs, the results so far are conflicting.…”
Section: Discussionmentioning
confidence: 99%